1974
DOI: 10.1136/pgmj.50.583.312
|View full text |Cite
|
Sign up to set email alerts
|

The use of anticoagulants in bacterial endocarditis

Abstract: Summary Early experience in the treatment of bacterial endocarditis with penicillin suggested that the addition of anticoagulants might improve results. This paper reports a patient with bacterial endocarditis who died from embolic cerebral damage after initiation of treatment with heparin. The evidence suggests that anticoagulants were responsible for her death and that bacterial endocarditis is a relative contra-indication to anticoagulant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1976
1976
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Other groups have reported an alarming incidence of cerebral hemorrhage. [79][80][81][82][83] A trial of 115 patients with IE who were randomized to aspirin treatment reported the effect of aspirin therapy on the risk of embolic events in IE (n 5 60, 325 mg/d) or placebo (n 5 55) for 4 weeks ( Table 3 , Table S2). 84 The addition of aspirin did not reduce the risk of embolic events, with 17 (28.3%) such events in the aspirin group vs 11 (20.0%) in the placebo group (OR, 1.62; 95% CI, provides a strong indication for anticoagulation, and when technically feasible, closure of the PFO.…”
Section: Patent Foramen Ovale and Atrial Septal Aneurysmmentioning
confidence: 99%
“…Other groups have reported an alarming incidence of cerebral hemorrhage. [79][80][81][82][83] A trial of 115 patients with IE who were randomized to aspirin treatment reported the effect of aspirin therapy on the risk of embolic events in IE (n 5 60, 325 mg/d) or placebo (n 5 55) for 4 weeks ( Table 3 , Table S2). 84 The addition of aspirin did not reduce the risk of embolic events, with 17 (28.3%) such events in the aspirin group vs 11 (20.0%) in the placebo group (OR, 1.62; 95% CI, provides a strong indication for anticoagulation, and when technically feasible, closure of the PFO.…”
Section: Patent Foramen Ovale and Atrial Septal Aneurysmmentioning
confidence: 99%
“…The operative mortality was 37%. Anticoagulants were given to three patients while atrial arrhythmias were being controlled; in two the outcome was favourable while the third died with massive intracranial haemorrhage; these cases and our own views on the use of anticoagulants in infective endocarditis have been reported by Kanis (1974). OUTCOME In all, 37 patients died, a mortality rate of 46%.…”
Section: Incidencementioning
confidence: 88%
“…This view continued until challenged by Lerner and Weinstein 29 who believed it wise to use antibiotic and anticoagulant. In 1974, Kanis 30 reported a patient with bacterial endocarditis who died from embolic cerebral damage after treatment with heparin. It would appear that it continues to be unwise to use anticoagulant in this situation.…”
Section: Treatment Related To the Heartmentioning
confidence: 99%